How social desirability impacts life satisfaction among Chinese youth: mediators of mental toughness and emotional intelligence - Lv, Fangyan; Ye, Zhanhang; Liu, Zicheng; Gan, Jing; Tan, Jingbin; Feng, Run; Abudurexiti, Burebiya; Yu, Meng; Gao, Dingguo (Frontiers in Psychiatry, 2024)
Social desirability has been recognized as a predictor of life satisfaction but it has yet to know the mechanism of this effect. This research aimed to explore the relationship between social desirability and life satisfaction, as well as the mediation effects of mental toughness and emotional intelligence.In Sample 1, we asked 1200 youths (12-24 years old) to complete an online questionnaire measuring social desirability, life satisfaction, mental toughness, and emotional intelligence. Results indicated that social desirability had a direct positive effect on youth's life satisfaction. In addition, mental toughness and emotional intelligence mediated the relationship between social desirability and life satisfaction, showing a chain role of mental toughness and emotional intelligence. A second sample (n = 750) was then used to verify the above findings, and similar results were found. These findings are consistent with our hypotheses, revealing the mechanisms of social desirability in relation to life satisfaction and the important role of mental toughness and emotional intelligence.